The Rights of Workers Who Voluntarily Resign Whose Wages Have Not Been Paid (Case Study of Supreme Court Decision Number 318 K/Pdt.Sus PHI/2023 - Naufal Abdul Majid; Arinto Nugroho (NOVUM : JURNAL HUKUM, 2024)
This research aims to analyze the rights of employees who voluntarily resign and whose wages have not been paid, through a case study of the Supreme Court decision number 318 K/Pdt.Sus-PHI/2023. This type of research is normative with a legislative, case, and conceptual approach. The technique for collecting legal materials is done through literature study and analyzed using a prescriptive technique. The research findings indicate that the judge's consideration of applying Article 50 of Government Regulation 35/2021, supported by the available evidence, states that employees who voluntarily resign are still entitled to unpaid wages and holiday allowances (THR), as well as severance pay. The research also concludes that employees who voluntarily resign should also be entitled to compensation for rights. The legal consequence of this decision is the annulment of the previous ruling, which rejected the lawsuit in its entirety. Consequently, the Defendant is obligated to pay the unpaid wages and THR, as well as the severance pay, to the Plaintiffs.